Given f(x) = x + 2, g(x) = 2x + 3, h (x) = 3x + 4 for x E R find (i) fo(goh) (ii) (fog)oh.
Answers
Answered by
16
Answer :
(i) fo(goh)(x) = 6x + 13
(ii) (fog)oh(x) = 6x + 13
Solution :
→ Given :
• f(x) = x + 2 , x € R
• g(x) = 2x + 3 , x € R
• h(x) = 3x + 4 , x € R
→ To find :
• fo(goh)(x) = ?
• (fog)oh(x) = ?
(i) fo(goh)(x) = ?
Firstly ,
Let's find goh(x) .
Thus ,
→ goh(x) = g{h(x)}
→ goh(x) = g(3x + 4)
→ goh(x) = 2(3x + 4) + 3
→ goh(x) = 6x + 8 + 3
→ goh(x) = 6x + 11
Now ,
→ fo(goh)(x) = f{goh(x)}
→ fo(goh)(x) = f(6x + 11)
→ fo(goh)(x) = 6x + 11 + 2
→ fo(goh)(x) = 6x + 13
(ii) (fog)oh(x) = ?
Firstly ,
Let's find fog(x) .
Thus ,
→ fog(x) = f{g(x)}
→ fog(x) = f(2x + 3)
→ fog(x) = 2x + 3 + 2
→ fog(x) = 2x + 5
Now ,
→ (fog)oh(x) = (fog){h(x)}
→ (fog)oh(x) = (fog)(3x + 4)
→ (fog)oh(x) = 2(3x + 4) + 5
→ (fog)oh(x) = 6x + 8 + 5
→ (fog)oh(x) = 6x + 13
Hence ,
fo(goh)(x) = (fog)oh(x) = 6x + 13
Answered by
1
Answer:
Step-by-step explanation:
Similar questions